Alternative model for financing micro enterprises in Malaysia - Mohd Thas Thaker, Mohamed Asmy; Mohammed, Mustafa Omar; Duasa, Jarita; Abdullah, Moha Asri (2014)
The contributions of micro enterprises (MEs) in Malaysia can be measured in terms of some inter-related issues: economic, social and political. Despite these recognized importance and the largest contributor to SMEs - the micro enterprises have hardly considerable financing assistance. MEs are considered as risky business and strict loan conditions have been imposed on them such as strict collateral requirement, high cost of financing, strict documentation requirement and good business track record. Unfortunately, most of them cannot fulfil these conditions and continue to face the problem of accessing finance. Thus, the present study has used content analysis to critically survey the literature on the subject. This study aims to propose an Integrated Cash Waqf Micro Enterprise Investment (ICWME-I) Model as a solution to overcome MEs’ financial constraints and enhance their activities that contribute to the national income. The study concludes with some suggestions for future research.